2015
DOI: 10.1080/15476278.2015.1093268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibroin sponge coating on in vivo performance of knitted silk small diameter vascular grafts

Abstract: ABSTRACT. Vascular grafts under 5 mm or less in diameter are not developed due to a problem caused by early thrombus formation, neointimal hyperplasia, etc. Bombyx mori silk fibroin (SF) which has biodegradability and tissue infiltration is focused as tube and coating material of vascular grafts. Coating is an important factor to maintain the strength of the anastomotic region of vascular grafts, and to prevent the blood leak from the vascular grafts after implantation. Therefore, in this research, we focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…The simplest technical approach to create at least an additional layer is to coat the textile tubular scaffold with a film-forming biocompatible polymer (SF or gelatin) (Fukayama et al, 2015; Yamamoto et al, 2016). The use of SF microfibers as scaffold material and of SF aqueous solution as coating showed advantages in terms of enhanced in vivo endothelialization, which corresponded to improved graft performance (e.g., medium-to-long term patency).…”
Section: Introductionmentioning
confidence: 99%
“…The simplest technical approach to create at least an additional layer is to coat the textile tubular scaffold with a film-forming biocompatible polymer (SF or gelatin) (Fukayama et al, 2015; Yamamoto et al, 2016). The use of SF microfibers as scaffold material and of SF aqueous solution as coating showed advantages in terms of enhanced in vivo endothelialization, which corresponded to improved graft performance (e.g., medium-to-long term patency).…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, it has been used as an excellent biomaterial because of the ability to fabricate silk into a wide range of materials with tunable mechanical and degradation properties. 11,12 In the last decade, our group [13][14][15][16][17][18][19][20][21][22] and other groups [23][24][25][26] have shown that SF is an excellent candidate for vascular grafts on the basis of in vivo implant data with rats and/or dogs. SF vascular grafts prepared in our studies [15][16][17][18][19][20][21][22] consist of the SF fiber base coated with the SF sponge.…”
Section: Introductionmentioning
confidence: 99%
“…ECs and SMCs were observed onto the luminal area of the graft for proximal and distal parts, but contrarily to the rat models no ECs were visible in the middle portion even after 1 year. In 2015, PGDE was used again by Fukayama et al, 83 who made double-raschel knitted silk scaffolds coated with silk and PGDE sponges for studying the impact of silk concentration in the sponges. After implanting the grafts (1.5 mm in diameter, 1 cm long) for up to 3 months in rat models, they showed that the ideal concentration was 1.5% of silk, regarding stenosis, tissue infiltration, and intimal hyperplasia.…”
Section: Vascular-shaped Scaffoldsmentioning
confidence: 99%